Experiential Marketing's Impact on Customer Loyalty Through Satisfaction : Evidence from Bank Syariah Indonesia - Afrida Nurfaizah Amara; Budi Sukardi; Nur Hidayah Al Amin (Masoem University, 2026)
The development of the Islamic banking industry in Indonesia has triggered intense competition, requiring Islamic banks to innovate in their marketing strategies to maintain customer loyalty. This study examines the effect of experiential marketing (dimensions of sense, feel, think, act, and relate) on customer loyalty at Bank Syariah Indonesia (BSI), with customer satisfaction as an intervening variable. The study used a quantitative cross-sectional design on 100 active customers of BSI Karanganyar Branch, selected through stratified random sampling. Primary data were collected via a structured questionnaire with a 5-point Likert scale, analyzed using multiple linear regression and path analysis to test direct and indirect effects. The results show that experiential marketing simultaneously has a significant effect on customer satisfaction and loyalty. Customer satisfaction proved to be a strong mediator in this relationship, with the dimensions of think, act, and relate showing a dominant influence. These findings confirm the mediation mechanism of satisfaction in building loyalty in the context of Islamic banking. The study recommends that BSI strengthen creative thinking experiences, positive habit formation, and emotional connections to maximize satisfaction and long-term loyalty.